The use of genetic engineering techniques to improve the lipid composition in meat, milk and fish products: a review. (12th December 2014) - Świątkiewicz, S.; Świątkiewicz, M.; Arczewska-Włosek, A.; Józefiak, D.
Abstract : The health-promoting properties of dietary long-chain n-3 polyunsaturated fatty acids (n-3 LCPUFAs) for humans are well-known. Products of animal-origin enriched with n-3 LCPUFAs can be a good example of functional food, that is food that besides traditionally understood nutritional value may have a beneficial influence on the metabolism and health of consumers, thus reducing the risk of various lifestyle diseases such as atherosclerosis and coronary artery disease. The traditional method of enriching meat, milk or eggs with n-3 LCPUFA is the manipulation of the composition of animal diets. Huge progress in the development of genetic engineering techniques, for example transgenesis, has enabled the generation of many kinds of genetically modified animals. In recent years, one of the aims of animal transgenesis has been the modification of the lipid composition of meat and milk in order to improve the dietetic value of animal-origin products. This article reviews and discusses the data in the literature concerning studies where techniques of genetic engineering were used to create animal-origin products modified to contain health-promoting lipids. These studies are still at the laboratory stage, but their results have demonstrated that the transgenesis of pigs, cows, goats and fishes can be used in the future as efficient methods of production of healthy animal-origin food of high dietetic value. However, due to high costs and a low level of public acceptance, the introduction of this technology to commercial animal production and markets seems to be a distant prospect.